Produktivitas dan Luas Lahan Minimal Petani Padi Sawah Lebak di Kabupaten Ogan Ilir - Komala Sari; Ahmad Febriyansyah (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Sari et al, 2018. Productivity and an Enlarge Minimum Land Area of Paddy’s Farmers in Swamp Land of the Ogan Ilir Regency. JLSO 7(2):185-195.South Pemulutan is one of the sub-districts in Ogan Ilir Regency which has swamp paddy fields potential to be developed. Unfortunately, the use of production factors which applied by the farmers has not been maximized. Therefore, proper management by using production factors efficiently and effectively can increase productivity and maintain the sustainability of their farm. Moreover, the aims of this research were (1) to analyze the factors which affect the low productivity of the swamp paddy fields, (2) to calculate the percentage of an income of the swamp paddy fields’ farmer which can fulfill their household outcome, (3) to calculate the minimum land area of the swamp paddy fields of the farmer. The method were used in this research was survey method. The sample of the farmers which taken in this study were 30 farmers from 187 farmers which works on swamp paddy fields in Lebak Pering village. The data was gathered consist of the primary data and the secondary data. The result of this research showed (1) factors which extremely affected toward swamp paddy fields productivity in Lebak Pering village was the largest of the area, seed variety, the used of urea fertilizer, the experiences of the farmer, while those that have no effect are the used of SP-36 fertilizer, NPK fertilizer and then the pesticides. (2) The contribution of swamp paddy fields farmers’ income to farmers' consumption expenditure were 60.28%. (3) The minimum land area that suggested to be cultivated by the farmer is 1 hectare and if the farmer only relies on their swamp paddy fields farming, then the minimum land area that suggested to be raised by the farmer is 1.66 hectares.